Bangladesh, 1971, los juicios por crímenes de guerra y el control de la narrativa: ¿el Estado o la empresa colaboracionista? (Bangladesh, 1971, war crimes trials and control of the narrative: the State or collaborative enterprise?) - Morrison, Wayne (2013)
Bangladesh was born in a violent struggle many label genocide. Few were ever prosecuted. The article considers the issue in terms of competing narratives and the issue of ownership of ‘truth’ and the contribution of images of 1971 to the constitution of Bangladesh. Since 2010 belated war crimes trials have been help for local collaborators; the accused mainly come from Islamic political parties and the verdicts have spurred popular protests resulting in violent confrontations. The trials have been criticised as political trials aimed at eliminating political opposition rather than achieving justice and healing historical wounds. Is this a defining moment for Bangladesh that can change the form of politics – one that breaks the hold of the state over the narrative and ushers in a new form of collaborative enterprise - or is this the occasion for a resurgence of religious sentiments that weakens the secular constitution and increases social instability? Bangladesh nació en una violenta lucha que muchos califican de genocidio. Pocos fueron juzgados. Su legado continúa. Este artículo considera el asunto en términos de su contribución a la imaginería de la constitución de Bangladesh y el impacto que tienen las imágenes de la lucha. Desde 2010, los tardíos juicios por crímenes de guerra han estado apoyados por colaboracionistas nacionales; los acusados provienen principalmente de los partidos políticos islámicos y los veredictos han resultado en protestas populares que causaron violentas confrontaciones. Los juicios han sido criticados por ser juicios políticos, que apuntan a eliminar la oposición política en lugar de conseguir justicia y sanar las heridas históricas. ¿Es este un momento definitivo para que Bangladesh pueda cambiar la forma de la política –una que rompa el control del Estado sobre la narrativa y los encargados del orden, por una forma nueva de empresa colaboracionista– o es ésta la ocasión para el resurgimiento de sentimientos religiosos que debiliten la Constitución secular e incrementen la inestabilidad social?